2003
DOI: 10.1046/j.0022-4537.2003.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the Socioeconomic Ladder: Low‐Income Women's Perceptions of Class Status and Opportunity

Abstract: This study examined how 69 low-income women enrolled in an educational training program perceived social class and upward mobility. Participants identified their social class during childhood, their current status, and their anticipated post graduate status. Beliefs about income inequality and attributions for wealth and poverty were also assessed. Respondents expected to achieve middle class status and perceived higher education as a route to upward mobility, although the accessibility of post-secondary progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 26 publications
(38 reference statements)
5
88
0
1
Order By: Relevance
“…Conceptualizations of SES markers are somewhat unique developmentally. Whereas adults identify social class primarily by financial resources and, to a lesser extent, housing, occupation, and education (Bullock and Limbert 2003), an exploratory study with a sample of working class and upper-middle class adolescents found that adolescents tend to identify family money and lifestyle as well as parental occupation and education as the most important markers for determining social class (Goodman et al 2000). Thus, when considering how adolescents perceive their own social class and their SES match (or mismatch) with their schoolmates, the markers identified by Goodman and colleagues are informative.…”
Section: Race/ethnicity Socioeconomic Status and Students' Developmmentioning
confidence: 99%
“…Conceptualizations of SES markers are somewhat unique developmentally. Whereas adults identify social class primarily by financial resources and, to a lesser extent, housing, occupation, and education (Bullock and Limbert 2003), an exploratory study with a sample of working class and upper-middle class adolescents found that adolescents tend to identify family money and lifestyle as well as parental occupation and education as the most important markers for determining social class (Goodman et al 2000). Thus, when considering how adolescents perceive their own social class and their SES match (or mismatch) with their schoolmates, the markers identified by Goodman and colleagues are informative.…”
Section: Race/ethnicity Socioeconomic Status and Students' Developmmentioning
confidence: 99%
“…The majority of interviewees had no close peers or family members who had attended four-year colleges. In fact, studies suggest that many low-income mothers would like to pursue a college degree but most doubt their ability to attain one (Bullock and Limbert 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Many struggle fulfill work and family responsibilities while patching together childcare arrangements to cover classroom and working hours. (Mason 2002;Bullock and Limbert 2003;Deprez, Butler and Smith 2004;Christopher 2005). Even those students who qualify for subsidized childcare often have difficulty retaining childcare vouchers when they return to school.…”
Section: Recognized Obstacles To Higher Education For Low-income Singmentioning
confidence: 99%
“…These two authors are particularly well-suited to the task: They have been tireless advocates and activists on behalf of a psychological agenda that includes attention to social class; their own research documents the critical ways in which class inequality and attitudes about social classrelated issues are a fundamental part of-and fundamentally shape-our psychological experiences (see, e.g., Bullock 1999;Bullock and Limbert 2003;Bullock and Waugh 2005;Lott 2001Lott , 2002Lott and Bullock 2001); and they have taught hundreds of students about issues of social class (including how class intersects with gender and race). They worked very hard on and helped secure the eventual passage of the American Psychological Association's (APA) Resolution on Poverty and Socioeconomic Status, originally published in 2000 and reproduced in the "Appendix" of their book.…”
mentioning
confidence: 99%